PEDAGANG BERMOTOR : KARAKTERISTIK BARU PEDAGANG KAKI LIMA DI KAWASAN PENDIDIKAN TEMBALANG, SEMARANG - Katarina Chandra Hapsari (Badan Perencanaan Pembangunan Daerah Kota Semarang, 2017)
A street vendors becomes one of the most prominent occupations in the informal sector where the informal sector depends on formal activity. Street food sellers become an alternative job when people cannot enter/join to the formal sector and they have to fullfil their needs. The development of Tembalang educational areas as well as the large number of migrant communities makes the emergence of increasingly increasing street vendorsin which the presence of street food sellers help to fulfil consumer needs. Over time, the number of street food sellers is increasing which makes the beauty and structuring of the city disturbed. Traffic jam is also the impact of the presence of unregulated street vendorswho occupy the side road and have no parking area for consumers. The increasing number of street vendorsmakes the competition among them to attract consumers, one of them is innovation in physical trading facilities, where street food sellers currently choose to use motor vehicles as a means of trading.